Evaluation Of The Field Work Practice Program (Pkl) Using The Discrepancy Evaluation Model (Dem) In The Computer Engineering And Informatics Expertise Program At Smk Negeri 7 Bandar Lampung - Aiza Nabila Hasan; Ivan Hanafi; Riyadi Riyadi (Journal of Social Research, 2024)
The 2003 National Education System Law outlines the purpose of national education, emphasizing vocational education as secondary education aimed at preparing students for specific fields of work. However, the COVID-19 pandemic has created challenges in achieving these goals, prompting a need for evaluation and solutions. To address this, a program evaluation is proposed, focusing on analyzing the Industrial Work Program (PKL) in terms of design, implementation, process, and outcomes. The evaluation aims to assess the alignment between program objectives and actual results, considering factors such as program design, HR requirements, implementation scope, street vendors' involvement, and outcomes for schools, students, and industry partners. The Discrepancy Evaluation Model (DEM) by Malcom Provus is chosen for its ability to compare expectations with reality. The evaluation will employ both quantitative and qualitative methods, utilizing questionnaires, observations, interviews, and document analysis. Qualitative data analysis involves activities such as data reduction, display, validation (triangulation), and conclusion drawing, while quantitative analysis utilizes descriptive percentage analysis. The research seeks to generate recommendations that improve education quality and program evaluation practices, particularly in ICT-based competency development during the pandemic transition. By providing a detailed evaluation, the study aims to offer actionable insights for enhancing the PKL program's effectiveness and contributing to educational advancement.